Physical and Mechanical Properties of Sal (Shorea robusta) from Fourteen Different Localities in India - Sekhar, A. C.; Rajput, S. S. (Indian Forester, 1968)
Shorea robusta (sal) occurs widely in several parts of the country and is used for numerous purposes. In the present paper the available data on Physical and Mechanical properties of sal in "green" and "air-dry" condition from 14 different localities of India obtained from test results of 5 logs from 5 different trees selected from each locality, has been presented in metric units alongwith the growth conditions. The data of some selected important properties, viz., Fibre stress at Elastic limit, Modulus of rupture, Modulus of Elasticity, Crushing Stress, Hardness and Height of drop in Impact bending have been analysed to study the influence of locality of growth and variation of strength of above properties from one locality to another have been evaluated and discussed. On the basis of investigations, it has been observed that strength properties vary from locality to locality and the same (localities) have been roughly classified into three groups yielding significantly different quality of wood.